RELATIONSHIP BETWEEN CIGARETTE SMOKING AND NASOPHARYNGEAL CARCINOMA - Ibrahim Irsan Nasution; Ramsi Lutan; Delfitri Munir; Arlinda Sari Wahyuni (TALENTA PUBLISHER, 2019)
Introduciton Since then the pathogenesis of NPC has been intensively studied, specifically aimed at geography and racial variation. In recent years many environmental and biological factors have shown a risky relationship to the occurrence of NPC and the latest research results indicate the role of genetic and viral factors in the development of this disease Objectives Etiology of nasopharyngeal cancer (NPC) is multifactorial, and many of these factors overlap where one factor may occur together with other elements as a cause. Cigarette smoking is thought to also play a role in the development of NPC. Methods The study design was in case of control with an analytical approach during February-October 2007. To find out the relationship between Cigarette smoking NPC, a case-control study was conducted, with a sample of 96 patients with NPC as case and 96 people as a control. Case group and control samples were taken from RSUP H. Adam Malik Medan and RSU Dr. Pirngadi Medan. Results The majority of NPC patients are: Men (compared with women 2.84: 1), 50-59 years (29.2%), and farming (32.3%). The Batak ethnic is the largest ethnic group suffering from NPC 54 people (56.3%) and followed in the second place the most are Javanese (29.2%). The most histopathological type is WHO type 3 (38.6%). Most stages were III (58.4%), followed by stage IV (40.6%), stage II (1%), and there was none of stage I.In univariate logistic regression showed a significant relationship between smokers with consumption of cigarettes 11-20 cigarettes per day with OR=2.530 (p=0.021) with the occurrence of NPC. However, in the multivariate logistic regression analysis, the number of cigarettes per day did not show a significant relationship (p=0.587). The results of multivariate logistic regression analysis, nasopharyngeal carcinoma were significantly associated with people who had started smoking before the age of 20 years (p=0.000; OR 5.35 and CI 95% 2.290-12.499), consuming habits of salted fish before 10 years of age with sometimes frequency consumption of salted fish p=0.000; OR 7.766 (95% CI 2.937-20.538), often p=0.000; OR 16.515 (95% CI 5.3000-51.463), and the habit of using firewood p=0.014; OR 3.147 (95% CI 1.260-7.860). There was no significant relationship between the duration of cigarette smoking (p=0.293), a number of cigarettes (p=0.021) and the types of cigarettes smoked (p=0.081) with the incidence of NPC. Conclusion Cigarette smoking as a risk factor for NPC cannot act stand-alone as a risk factor, but there is a role for other factors that also influence as a risk factor.